New Philippine record of South American sailfin catfishes (Pisces: Loricariidae) - Chavez, Joel M. (Animo Repository, 2006)
A taxonomic and biogeographic study of the introduced suckermouth armored catfishes locally known as "janitor fish" is briefly described. Specimens were collected from five sites in the Laguna de Bay basin and were examined for 19 meristic and 37 morphometric characters and other external features including coloration. Results were compared with existing literature on fishes in the family Loricariidae. Examination revealed that specimens of janitor fish, previously reported as Hypostomus plecostomus, actually belong to the genus Pterygoplichthys, family Loricariidae. Collected specimens consisted of two species-Pterygoplichthys disjunctivus and Pterygoplichthys pardalis. Both species were collected from the five sites except in Pasig River where only P. disjunctivus was collected. Copyright © 2006 Magnolia Press.